Comparative analysis of economic systems' goals: ranking approach. (17th June 2019) - Katkov, Alexander
Each economic system has the same mission and the same list of major economic goals but every economic system has its own order of prioritisation of these goals. In this article the author first will select the list of four main economic goals common to every economic system. Then, after a brief analysis of three main economic systems - pure market, pure command, and mixed economies - I will establish a theoretically defined goals ranking order for pure market and pure command economies. Finally, I will compare an empirically evaluated ranking order of economic goals for a few selected countries with the theoretically defined ranking order. The interpretation of calculated coefficients of correlations could be used for further comparative analysis of economic policies of different countries.